Drying of Porous Particles Wetted with a Liquid Mixture in a Fluidized Bed With (Journal of Science and Technology, 2015)
Although water is often the only solvent used, there are several important industrial applications where a mixture of liquids with different volatilities are involved. In such cases not only the drying rate but also the Variation of the composition of the liquid contained in the solids with the moisture content of the particles is of interest. This could reveal whether or not a partial preferential removal of one component or the other is possible in the course of the drying. In this study a 1 m long, 0.2m diameter fluidized bed with heated walls and various mixtures of iso-propanol and water was used. Results obtained indicate that mild drying conditions promote more selectivity since the process-controlling liquid-side mass trans-fer resistance, increases with the severity of drying.